The cardiovascular and respiratory health of people with schizophrenia - Filik, R.; Sipos, A.; Kehoe, P. G.; Burns, T.; Cooper, S. J.; Stevens, H.; Laugharne, R.; Young, G.; Perrington, S.; McKendrick, J.; Stephenson, D.; Harrison, G. (Acta psychiatrica Scandinavica, 2006)
Objective:  To examine the cardiovascular and respiratory health of people with severe mental illness (SMI) and compare findings with the Health Surveys for England. Method:  A prospective, multi‐centre observational prevalence study of 602 patients with schizophrenia‐related psychoses carried out in six locations across the UK over 24 months. Results:  Compared with general population subjects, people with SMI reported higher rates of angina and respiratory symptoms and had poor lung function. Much of this increased risk could be explained by lifestyle risk factors; there were increased levels of obesity among younger people with SMI. Conclusion:  Key indicators of the cardiovascular and respiratory health of people with SMI are poor compared with those of the general population. Care plans should prioritize interventions to attenuate lifestyle risk factors. Evidence of increasing obesity in younger patients is of particular concern, predicting even greater health needs in the future.